2016
DOI: 10.1063/1.4954681
|View full text |Cite
|
Sign up to set email alerts
|

Tunable plasmonic-lattice mode sensors with ultrahigh sensitivities and figure-of-merits

Abstract: We study the application of plasmonic lattice modes of arrays of closely packed large metallic nanodisks for chemical and biological sensors with ultrahigh sensitivity and refractive index dynamic range. Our results show that by changing the refractive index of the environment the narrow spectral features associated with these collective modes can be shifted by about 250 nm, going from visible (∼650 nm) to infrared (∼900 nm) range without any mode degradation. We attribute this shift to the refractive-index en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…232 Biological sensing based on the transition from LSPRs to SLRs was studied in arrays of gold nanoantennas covered by an ultrathin silicon layer by Gutha et al 233 They showed that SLRs may lead to very high sensitivities to small changes of refractive index; they did this by detecting biomonolayers and streptavidinconjugated semiconducting quantum dots. Sadeghi et al 234 investigated the application of SLRs of arrays of large metal nanodisks to chemical and biological sensing. They demonstrated that narrow SLRs could be shifted from the visible (∼650 nm) through to the infrared (∼900 nm) range by altering the environment's refractive index.…”
Section: Biosensing and Biorecognitionmentioning
confidence: 99%
“…232 Biological sensing based on the transition from LSPRs to SLRs was studied in arrays of gold nanoantennas covered by an ultrathin silicon layer by Gutha et al 233 They showed that SLRs may lead to very high sensitivities to small changes of refractive index; they did this by detecting biomonolayers and streptavidinconjugated semiconducting quantum dots. Sadeghi et al 234 investigated the application of SLRs of arrays of large metal nanodisks to chemical and biological sensing. They demonstrated that narrow SLRs could be shifted from the visible (∼650 nm) through to the infrared (∼900 nm) range by altering the environment's refractive index.…”
Section: Biosensing and Biorecognitionmentioning
confidence: 99%
“…Even though the bulk FoM of our grapheneplasmon based sensor is large, it is not the largest achieved in the literature [23]. However, we emphasize that the main strength of our plasmon sensor is its ability to sense refractive index changes that occur very close to the surface.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, they found surface lattice resonances (SLRs) with high sensitivities to small changes of refractive index [10]. Sadeghi et al found that narrow SLRs could be shifted by changing the environmental refractive index based on the arrays of large nanodisks for chemical and biological sensing [11]. Additionally, plasmonic biosensing offers a new way to detect coronavirus with low-cost and rapid detection.…”
Section: Introductionmentioning
confidence: 99%